The Impact of Operational Performance and Pricing Policy on Purchase Intention for Economy-Class Train Services - Lestari, Lestiyanti; Yuaniko, Yuaniko (SAN Scientific, 2026)
This study aims to analyze the effect of operational performance and pricing policy on purchase intention for long-distance economy-class train tickets at Bekasi Station. Fluctuations in passenger numbers and relatively low growth compared to market potential indicate unstable consumer purchase intention. Operational issues such as delays and facility complaints, as well as perceptions of price-value mismatches, are assumed to influence consumer decisions. A quantitative survey approach was employed using primary data collected from 76 economy-class passengers. Data were analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS. The results reveal that operational performance and pricing policy have a positive and significant effect on purchase intention, both partially and simultaneously. The coefficient of determination shows that these two variables explain 97.5% of the variation in purchase intention. The findings conclude that improving punctuality, service quality, and facility comfort, and implementing competitive, value-based pricing strategies are crucial to increasing consumer interest. Managerially, the study contributes practical insights for railway operators in designing operational improvements and adaptive pricing strategies to enhance competitiveness and passenger demand.